Floral anatomy of Neotropical species of Mayacaceae - Silveira de Carvalho, Maria Luiza [UNESP]; Nakamura, Adriana Tiemi [UNESP]; Sajo, Maria das Gracas [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2009)
The Mayacaceae are a monogeneric monocot family of herbs that grow on swampy areas in the Americas and in Africa. Both the number of species constituting the family and its inter-familial relationships are unclear. By describing and comparing the floral anatomy of Mayaca fluviatilis, M. fluviatilis f. kunthii, M. longipes and M. sellowiana we have identified some features that delimit the species. These include: arrangement of flowers on the stem, shape of stamens, size of apical pores, disposition of microsporangia, number of Ovules and shape of the stylar canal. We concluded that M. fluviatilis f. kunthii should be considered as a species (M. kunthii) rather than a forma. Other characters such as number of stamens and microsporangia, placentation, ovule type and cell numbers in the pollen grain support the placement of the Mayacaceae within Poales. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: Anatomy; Flowers; Mayaca; Monocots; Morphology; Poales